Compliance with Australian stroke guideline recommendations for outdoor mobility and transport training by post-inpatient rehabilitation services: an observational cohort study - McCluskey, Annie; Ada, Louise; Kelly, Patrick J.; Middleton, Sandy; Goodall, Stephen; Grimshaw, Jeremy M.; Logan, Pip; Longworth, Mark; Karageorge, Aspasia (BioMed Central, 2015)
Background: Community participation is often restricted after stroke, due to reduced confidence and outdoor mobility. Australian clinical guidelines recommend that specific evidence-based interventions be delivered to target these restrictions, such as multiple escorted outdoor journeys. The aim of this study was to describe post-inpatient outdoor mobility and transport training delivered to stroke survivors in New South Wales, Australia and whether therapy differed according to type, sector or location of service provider.